If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -1x(2 + 4) + 40 = 28 Combine like terms: 2 + 4 = 6 -1x(6) + 40 = 28 Reorder the terms for easier multiplication: -1 * 6x + 40 = 28 Multiply -1 * 6 -6x + 40 = 28 Reorder the terms: 40 + -6x = 28 Solving 40 + -6x = 28 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-40' to each side of the equation. 40 + -40 + -6x = 28 + -40 Combine like terms: 40 + -40 = 0 0 + -6x = 28 + -40 -6x = 28 + -40 Combine like terms: 28 + -40 = -12 -6x = -12 Divide each side by '-6'. x = 2 Simplifying x = 2
| a-10=-5a+2 | | -53=-7x+3 | | -8+4x=8 | | -53=-7x | | -4x-2+6=9 | | -2x+4ifx=7 | | 50m+2y=7y | | -4x+-2+6=9 | | 4x+-2x+6=9 | | 2x+4=5x+9 | | -9(x-1)=-36 | | 8=1-2n+5 | | 5/3w-7/4=-w-4/3 | | -6-3x=27 | | -45=9(-2+x) | | -4x+18=-6 | | -x+x-4=2 | | -3p=-27 | | 5a^2=25a | | 4w-5(2w-6)=10-(w-5) | | -0.6b+7+0.4b=19 | | x^2+y^2+10x+6y+34=0 | | 176=-16m | | -10(x-6)=70 | | x^2+y^2+10x+6y=-34 | | -8h+47=-1 | | x^2+y^2=-10x-6y-34 | | -15x+22=-38 | | 45+2(3-x)=2 | | 11-8z=69 | | (2x^2-11x-15)/(x+7) | | 4q-17=17 |